"Plug‐and‐Go"‐Type Liquid Diode: Integrated Mesh with Janus Superwetting Properties. Issue 19 (6th October 2016) - Li, Hao; Cao, Moyuan; Ma, Xiaoyan; Zhang, Yaxin; Jin, Xu; Liu, Kesong; Jiang, Lei
Abstract : Unidirectional liquid transportation is an essential process for some creatures, and it has important applications in the field of wastewater purification, liquid manipulation, etc. However, existing materials capable of unidirectional liquid transportation are rare and lack diversity and composability of membrane pore size. A novel Janus superwetting mesh is fabricated by integrating superoleophobic and superoleophilic surfaces underwater. Oil droplets can penetrate through the Janus mesh from the superoleophobic side to the superoleophilic side but are blocked from the reverse direction underwater. This Janus mesh can be assembled into a valvelike liquid diode, which makes it convenient for use in underwater unidirectional oil transportation. This work should serve as a source of inspiration for the construction of novel materials and corresponding devices with practical applications in oil/water separation, microfluidics, and other intelligent systems. Abstract : A Janus super‐wetting mesh is fabricated by integrating underwater superoleophobicity and superoleophilicity. An oil droplet can penetrate through the Janus mesh from the superoleophobic side to the superoleophilic side but is blocked from the reverse direction underwater. This research presents a novel and practical solution for underwater unidirectional oil transportation.